Pengembangan Elektronik-Lembar Kerja Peserta Didik (E-LKPD) dengan Pendekatan Pendidikan Matematika Realistik Indonesia Berbantuan Liveworksheets - Amaliah, Fanny; Bulan, Defina; Bestari, Hendra (MAJAMATH: Jurnal Matematika dan Pendidikan Matematika, 2024)
The purpose of this study is to find out the development of E-LKPD, the feasibility, effectiveness and practicality of E-LKPD with the PMRI Approach assisted by Liveworksheets. This research is an R&D research with the ADDIE model. The data collection technique is questionnaires and tests. The data collection instruments are interview sheets, validation questionnaires by linguists, materials and media, teacher and student practicality questionnaires and test questions. The data was analyzed with a likert scale and N-Gain score. The validation score was 89.3% by material experts, 90% by media experts (very valid criteria) and 78% (valid) by linguists. The results of the assessment of the response of teachers were 92% and students 82% (Very Practicality criterion). Mathematical problem-solving skills were calculated with an N-Gain score obtained of 71% (Quite effective). The results of this study conclude that E-LKPD is suitable for use.